MULTICENTER DOUBLE-BLIND RANDOMIZED PLACEBO-CONTROLLED TRIAL OF THE SYMPTOM- AND STRUCTURE-MODIFYING EFFECT OF ALFLUTOP IN PATIENTS WITH KNEE OSTEOARTHROSIS. COMMUNICATION 1. EVALUATION OF THE SYMPTOM-MODIFYING EFFECT OF THE DRUG - Lyudmila Ivanovna Alekseeva; E P Sharapova; E A Taskina; N V Chichasova; G R Imametdinova; N A Shostak; N G Pravdyuk; L N Denisov (Научно-практическая ревматология)
Objective: to evaluate the symptom- and structure-modifying effect of alflutop versus placebo (PL) in patients with knee osteoarthrosis (OA).Subjects and methods. The trial enrolled 90 patients with knee OA (ACR criteria and Kellgren–Lawrence Stages II–III) and pain on walking ≥ 40 mm on a visual analogue scale (VAS) who signed their informed consent. The patients were randomly assigned to two groups: 1) 45 patients who received alflutop as 1-ml intramuscular injections for a 20-day cycle at a 6-month interval for 2 years (a total of 4 cycles during 2 years); 2) 45 patients who were given PL (isotonic sodium chloride) injections following the same pattern. As concomitant therapy ibuprofen was used in a dose of 600–1200 mg/day. The efficiency of treatment was evaluated using the OMERACT-OARSI criteria, changes in the three scales WOMAC, EQ-5D, pain and general health status (GHS) on VAS; 15-m walking time, and therapeutic efficiency assessment by the physician and patient. At the beginning and at the end of the investigation, knee joint X-ray and magnetic resonance imaging were performed and the time course of changes in the level of biochemical markers (CTX-II and COMP) was determined to evaluate the structure-modifying effect of alflutop. Adverse reactions were recorded at each visit. A Statistica 10.0 data package was used for statistical analysis.Results. At the end of the trial, the use of aflutop versus PL showed a significant pain reduction in an intent-to-treat population (p=0.003). Analysis of a per protocol population indicated that the pain reduction was more marked in the aflutop group. WOMAC showed that the differences between the groups in the absolute value of pain intensity reduction were significant. A significance stiffness reduction was seen in the alflutop group at Visit 3; no significant decrease was found in the PL group (p < 0.001). Improvements in joint function and reduction in joint WOMAC index were noted in the alflutop group after the first cycle of therapy and these remained throughout the follow-up (p = 0.001). At Visit 6, significantly better quality of life was observed only in the alflutop group (p = 0.0045). Analysis of the GHS scale revealed that the differences between the groups were significant (p = 0.03). In the alflutop and PL groups, the therapy respondents were 73 and 40%, (p = 0.001). Among the alflutop-treated patients, 79% reduced the daily dose of nonsteroidal anti-inflammatory drugs (NSAIDs) and 21% completely discontinued using them. In the PL group, only 23% needed daily lower intake of NSAIDs.Conclusion. The double-blind randomized placebo-controlled trial established the symptom-modifying effect of alflutop in patients with knee OA.